Collision Dynamics of Autonomous Drones in Confined Fluid Environments Using the Lattice Boltzmann Method - Chagas, Fabio Suim; Lopez-Flores, Marlon M.; Rosa, Paulo Fernando Ferreira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper introduces a novel simulation framework that couples a D3Q19 BGK Lattice Boltzmann Method (LBM) fluid solver with rigid-body drone models. This framework captures two-way momentum exchange between drones and fluid and models inter-drone collisions as perfectly elastic. We simulate swarms of 30–60 drones under periodic boundary conditions on 3D grids of up to 1303 cells across fluid densities from ρ=1.0 to 4.55. We perform statistical simulations (Spearman's rs. Kendall's T, confidence intervals) to evaluate and confirm collision frequency trends. Results show that collision frequency increases nonlinearly with swarm size, whereas fluid density has minimal impact. This work provides a validated tool for fluid-swarm simulations and offers insight into collision risks for drone swarms in confined fluid environments. The findings can provide new directions for optimizing autonomous drone operations, particularly in industrial inspections and aerial swarms in urban settings.